Where is the unseen fungal diversity hidden? A study of Mortierella reveals a large contribution of reference collections to the identification of fungal environmental sequences - Nagy, László G.; Petkovits, Tamás; Kovács, Gábor M.; Voigt, Kerstin; Vágvölgyi, Csaba; Papp, Tamás (The New phytologist, 2011)
Estimation of the proportion of undescribed fungal taxa is an issue that has remained unresolved for many decades. Several very different estimates have been published, and the relative contributions of traditional taxonomic and next-generation sequencing (NGS) techniques to species discovery have also been called into question recently. Here, we addressed the question of what proportion of hitherto unidentifiable molecular operational taxonomic units (MOTUs) have already been described but not sequenced, and how many of them represent truly undescribed lineages. We accomplished this by modeling the effects of increasing type strain sequencing effort on the number of identifiable MOTUs of the widespread soil fungus Mortierella. We found a nearly linear relationship between the number of type strains sequenced and the number of identifiable MOTUs. Using this relationship, we made predictions about the total number of Mortierella species and found that it was very close to the number of described species in Mortierella. These results suggest that the unusually high number of unidentifiable MOTUs in environmental sequencing projects can be, at least in some fungal groups, ascribed to a lag in type strain and specimen sequencing rather than to a high number of undescribed species.